Dual air-gap axial flux permanent magnet machines for flywheel energy storage systems - Nguyen, Trong Duy (2012)
More and more renewable distributed generation (DG) connected to the grid has brought about significant impacts on network system security and reliability. The employment of flywheel energy storage system (FESS) is an effective way to deal with the negative impacts of DG, such as in power smoothing, power leveling, voltage restoring, and energy recycling. Consequently, the research and development of the FESS together with its key-supporting components has become an interesting topic during the last decade. This thesis has dealt with the efficient and compact dual air-gap axial flux permanent magnet (AFPM) machines for use in the FESS. The key aspects on the design, analysis, implementation and control of the proposed AFPM machine are covered in this thesis in the sequence as follows: (1) Design of the dual air-gap AFPM machine for FESS; (2) Modeling of the proposed AFPM machine; (3) FEM analysis and model verification for the proposed AFPM machine; (4) Development of control system for the proposed AFPM machine; (5) Experimental implementation and analysis of the machine prototypes. The AFPM machines offer some unique features which have been exploited to employ in FESS applications. In this thesis, an efficient and compact dual air-gap AFPM machine optimized for use in FESS applications is proposed. The conceptual FESS based on the proposed AFPM machine is also briefly presented. The AFPM machine is composed of two separate single air-gap AFPM machines, having two sets of three-phase stator windings but requiring only a single power converter which supplies power for control of both axial force and electromagnetic torque. The application of this machine in FESS is realized by orientating its axial direction vertically and having its double-sided rotor to be the core of the flywheel. In addition, the availability of axial force control helps to minimize the vertical bearing force to improve the efficiency of the FESS. This thesis has also developed a multi-variable non-linear mathematical model for the proposed AFPM machine. Linearization has been performed to obtain the linear model for this machine and also to facilitate its control system. Three-dimensional finite element analysis have been carried out during the design of the machine and used to verify the machine design together with the effectiveness of its mathematical model. Control strategies under both position sensored and sensorless schemes have also been developed. The effectiveness of the control strategies has been verified by simulations and experimental tests on the fabricated machine prototypes.